A simple adherence test for detection of IgM antibodies in typhoid - Ong, L.Y.; Pang, T.; Lim, S.H.; Tan, E.L.; Puthucheary, S.D. (Microbiology Society, 1989)
A simple adherence test to detect IgM antibodies in patients with typhoid is described. The test utilises the IgM-"capture" approach, in which the test serum is applied to microtitration plate wells previously coated with anti-human IgM, followed by application of a stained Salmonella typhi antigen suspension which shows adherence in positive cases. By this test, 58 (95%) of 61 sera from confirmed cases of typhoid possessed IgM antibodies to the H or O or both antigens of S. typhi. In patients for whom a diagnosis of typhoid was based only on a significant Widal-test titre, 31 (41%) of 76 sera had IgM antibodies to the H or O or both antigens of S. typhi. Some cross-reactivity of the IgM antibodies was detected, especially with the O antigens of S. paratyphi A and B. A total of 82 sera from non-typhoidal fevers (leptospirosis, typhus, dengue fever) showed no reactivity in this test. In normal sera there was no detectable IgM to the O antigen of S. typhi and only a small number (3.9%) had low levels of IgM to the H antigen. The significance and potential importance of this simple, sensitive, specific and economical test is discussed.